Pluralism in the mass media: Can management participation help? - Nielsen, Richard P. (Journal of business ethics, 1984)
Concentration and lack of plurality of media control is significant and appears to be increasing. The potential danger to a democracy of a lack of plurality of media control is serious. There are opportunities for greater plurality and freedom of expression through professional employee decision making partcipation. There are practical precedents for professional employee management participation in the media. Therefore, professional media employee management participation deserves to be seriously considered. Limitations of the principle are also considered.